2017
DOI: 10.1590/1413-785220172501168600
|View full text |Cite
|
Sign up to set email alerts
|

Role of Different Hormones in the Pathogenesis and Severity of Adolescent Idiopathic Scoliosis

Abstract: Objective: To evaluate the hormonal profile of patients with adolescent idiopathic scoliosis (AIS) and its relationship to the severity of the curvature and quality of life . Method: Patients with scoliosis (Cobb angle above 10°), of both genders, diagnosed after 10 years of age were included, excluding those who presented other condition that could lead to scoliosis. Serum levels of 25-hydroxyvitamin D (25-OHD), cortisol and gastrin were correlated with Cobb angle and quality of life, measured by the SRS-3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…However, the median time spent by the former (AIS patients) in physical activities was slightly less than that spent by the controls [5]. Other studies have shown that osteopenia observed in AIS patients is related to vitamin D insufficiency and deficiency [10,103,104]. Longitudinal and cross-sectional studies have also demonstrated that the 25(OH)D level positively correlated with BMD in healthy children and adolescents [105-108].…”
Section: Osteopenia and Vitamin Dmentioning
confidence: 99%
“…However, the median time spent by the former (AIS patients) in physical activities was slightly less than that spent by the controls [5]. Other studies have shown that osteopenia observed in AIS patients is related to vitamin D insufficiency and deficiency [10,103,104]. Longitudinal and cross-sectional studies have also demonstrated that the 25(OH)D level positively correlated with BMD in healthy children and adolescents [105-108].…”
Section: Osteopenia and Vitamin Dmentioning
confidence: 99%
“…Adolescent idiopathic scoliosis (AIS) manifests as a three-dimensional (3D) deformity of the spinal column that occurs around puberty. Several factors such as genetics 1,2 , biomechanics 3 , morphology of the vertebral bones, intervertebral disc, and muscle physiology 49 , hormones 10,11 , environmental factors 12,13 , and neural system deficiencies 14,15 are considered as the underlying cause of the spinal deformity in AIS. While each of these factors explained part of the pathogenesis of this disease, none have proved to be its main or primary cause.…”
Section: Introductionmentioning
confidence: 99%
“…As an example, we reviewed all known papers reporting 25(OH)D in patients with AIS (n=5) (3,4,5,6,7). Only two papers indicated the race/ethnic distributions in the cohort.…”
Section: Categories Of Pitfallsmentioning
confidence: 99%